Handbook of activities to improve speaking skills for tenth grade students at unidad educativa mixta particular Sagrados Corazones, Salinas, province of Santa Elena, 2015-2016. - Valarezo Loor, Pablo Iván (2016)
This research focuses on the development of speaking skills for tenth grade students at Unidad Educativa Mixta Particular “Sagrados Corazones”, located in Salinas from the province of Santa Elena during the 2015-2016 school year, the methodology of this research is based on both approaches inductive and deductive. The deductive method was the basis to find all the general information needed for the research “Handbook of activities to improve speaking skills for tenth grade students at Unidad Educativa Mixta Particular “Sagrados Corazones”. The inductive method, helped to make some small observations in some of the activities seen during classes in order to improve speaking skills. Techniques used for collecting information were: survey, interviews and observation guides to have evidence of the process of learning English, especially the development of speaking skills at Unidad Educativa “Sagrados Corazones”. Speaking is a skill that students need to practice and domain it because of the necessity of sharing ideas and thoughts orally; therefore, it was important to develop a proposal that improve the oral communication and encourages students to use the target language orally.